'Helen' ; 'Antigone' ; 'Epicaste' ; 'eva' ; 'deka' ; 'ekato': Dangling Virgins, 1996 - E. Raskopoulos (Law Text Culture, 1998)
'Helen' ; 'Antigone' ; 'Epicaste' ; 'eva' ; 'deka' ; 'ekato' Dangling Virgins, 1996 gelatin silver print